(untitled) (Revista Internacional de Formação de Professores, 2021)
This study analyzed some gaps in the academic training of graduates from a Program in Chemistry. A survey of data was conducted using an online questionnaire, which revealed some limits in the initial training. Participants highlighted problems in the curriculum structure related to unnecessary prerequisites, disjointed disciplines, lack of reflection on teacher training, and scarcity of curricular components focused on teaching chemistry, revealing the course as an appendix of the bachelor’s degree. Another signaled gap was about the distance between school and university, with very few formative discussions regarding school environments.